2013
DOI: 10.1159/000353552
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Recurrent Sudden Sensorineural Hearing Loss

Abstract: Objective: Although the literature includes many reports of the causes, pathogenesis, diagnostic criteria, treatment, and prognostic factors of sudden sensorineural hearing loss (SSNHL), few studies have examined recurrent SSNHL. This prompted us to investigate recurrent SSNHL. Study Design: Retrospective study of the hearing results of patients with recurrent SSNHL. Methodology: We reviewed retrospectively the medical charts of 809 patients with SSNHL examined between January 2000 and June 2011 for informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…To be noted, even though 13% of our patients had recurrent hearing loss none of these patients had a history or symptoms for diagnosing Ménière’s disease and a vestibular schwannoma could be ruled out by MRI. Similar findings demonstrating poorer prognosis after recurrent episode of SSHL could also be shown by others [47, 48]. The reasons for this association could not be clarified yet.…”
Section: Discussionsupporting
confidence: 79%
“…To be noted, even though 13% of our patients had recurrent hearing loss none of these patients had a history or symptoms for diagnosing Ménière’s disease and a vestibular schwannoma could be ruled out by MRI. Similar findings demonstrating poorer prognosis after recurrent episode of SSHL could also be shown by others [47, 48]. The reasons for this association could not be clarified yet.…”
Section: Discussionsupporting
confidence: 79%
“…One of the children in our study had relapse after 3 months, the child had the ascending audiogram type and showed no recovery, but had completely recovered at the first onset. Park et al ( 25 ) reported 11 of 809 patients studied had recurrent idiopathic SSNHL, hearing recovery was poorer after a recurrent episode than that after the first episode.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the long‐term cumulative recurrence rate in the affected ear was 3.5%. In some studies, the recurrence rate has been reported to vary from 0.8% to 4.99%, but none of these studies has described the severity of hearing loss …”
Section: Discussionmentioning
confidence: 99%